Pengaruh Aerobic Exercise Terhadap Aktivitas Serum Creatin Kinase Myocardial Band (CK-MB) pada Lansia Pasca Stroke - Daba, Mariel; Fatria, Ilham; Padaallah, Ananda Patuh (Jurnal Kesehatan Andalas, 2024)
Stroke can cause changes in the heart, which are associated with excessive activation of the sympathetic nervous system as a response to damage occurring in the insular cortex. Cardiac biomarkers such as creatine kinase myocardial band (CK-MB) show increased levels in some patients with acute cerebrovascular accidents without direct cardiac injury. CK-MB activity has been found to increase in the early phase of patients with ischemic stroke, subarachnoid hemorrhage, and head trauma. Objective: To determined the effect of aerobic exercise on serum creatine kinase myocardial band (CK-MB) activity in elderly post-stroke patients. Methods: This was a pre-experimental study with a one-group pretest-posttest design. The study involved 16 elderly post-stroke respondents who received aerobic exercise using a static cycle at light to moderate intensity for 10-15 minutes, 2-3 times per week, over the course of 4 weeks. CK-MB activity was evaluated using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: There was a significant effect of aerobic exercise on serum CK-MB activity in elderly post-stroke patients, with a p-value of 0.000 or p < 0.05. The mean serum CK-MB level increased to 29.43µL, while the mean serum CK-MB level decreased to 23.12 µL after receiving aerobic exercise with a static cycle for 4 weeks. Conclusion: Aerobic exercise using a static cycle at light to moderate intensity for 10-15 minutes, 2-3 times per week, over the course of 4 weeks, had a significant effect on serum creatine kinase myocardial band (CK-MB) activity in elderly post-stroke. Keywords:  aerobic exercise, static cycle, creatine kinase-myocardial band, stroke, elderly